(untitled) (Perner’s Contacts, 2007)
“Proposal of Conflict Situation from Floating Vehicle” The paper describe to the proposal of dynamic method of monitoring of conflict situation from floating vehicle, which is based on Folprecht’s video analysis of conflict situations. The paper is based on experiences and proposals by staff and co-workers of Laboratory of Road Transport, Institute of Transport, VŠB-TU Ostrava.